Hematological parameters in patients with bloodstream infection: A retrospective observational study - Wei Tang; Wanchun Zhang; Xin Li; Juan Cheng; Zhou Liu; Qiang Zhou; Shihe Guan (Journal of Infection in Developing Countries)
Introduction: To date, the relationship between the causative pathogens and the changes of hematological parameters was rarely referred and deserves further investigation.